Melatonin Rescues Renal Mitochondria From Multiple Stressors–Induced Oxidative Stress - Alshahrani, Saeed; Sultan, Muhammad H.; Rashid, Hina; Alam, Firoz; Khan, Andleeb; Akhter, Mohammad Suhail; Qamri, Derayat; Beigh, Saba; Riyaz, Farhana (Basic & clinical pharmacology & toxicology, 2025)
ABSTRACT The renal system is a significant organ system vulnerable to stress due to its physiological function of toxin elimination. Exposure to a wide array of xenobiotics in humans causes deleterious effects in the kidneys. In the present study, we observed the toxic effect of a coexposure of bisphenol A and acetaminophen on the renal function and renal mitochondria of Wistar rats and its amelioration by melatonin. The animals were grouped and treated for 4 weeks as follows: (I) control; (II) melatonin; (III) bisphenol A; (IV) acetaminophen; (V) bisphenol A and acetaminophen; and (VI) bisphenol A, acetaminophen and melatonin. Coadministration of bisphenol A and acetaminophen exposure significantly impaired renal function, elevating creatinine (2.28 mg/dL), BUN (65.42 mg/dL) and uric acid (6.11 mg/dL), while increasing oxidative stress and inflammatory markers (CAT: 3.85‐μmol H2O2/min/mg protein, GPx: 189.57‐nmol NADPH/min/mg protein, GR: 96.62‐nmol NADPH/min/mg protein, MnSOD: 107.24‐nmol (−) epinephrine/min/mg protein, IL‐6: 1750 pg/mL, TNFα: 1677 pg/mL). Melatonin coadministration improved renal markers (creatinine: 1.60 mg/dL, BUN: 45.59 mg/dL, uric acid: 4.61 mg/dL) and partially restored antioxidant defences and inflammatory markers (CAT: 5.74‐μmol H2O2/min/mg protein, GPx: 422.74‐nmol NADPH/min/mg protein, GR: 136.91‐nmol NADPH/min/mg protein, MnSOD: nmol (−) epinephrine prevented from oxidation/min/mg protein, IL‐6: 1677 pg/mL, TNFα: 900 pg/mL). These findings suggest that melatonin mitigates bisphenol A and acetaminophen‐induced renal damage by enhancing antioxidant defences and reducing inflammation.